Circulating Non-Coding RNAs as Indicators of Fibrosis and Heart Failure Severity - Veronika Boichenko; Victoria Maria Noakes; Benedict Reilly-O’Donnell; Giovanni Battista Luciani; Costanza Emanueli; Fabio Martelli; Julia Gorelik (Cells)
Heart failure (HF) is a leading cause of morbidity and mortality worldwide, representing a complex clinical syndrome in which the heart’s ability to pump blood efficiently is impaired. HF can be subclassified into heart failure with reduced ejection fraction (HFrEF) and heart failure with preserved ejection fraction (HFpEF), each with distinct pathophysiological mechanisms and varying levels of severity. The progression of HF is significantly driven by cardiac fibrosis, a pathological process in which the extracellular matrix undergoes abnormal and uncontrolled remodelling. Cardiac fibrosis is characterized by excessive matrix protein deposition and the activation of myofibroblasts, increasing the stiffness of the heart, thus disrupting its normal structure and function and promoting lethal arrythmia. MicroRNAs, long non-coding RNAs, and circular RNAs, collectively known as non-coding RNAs (ncRNAs), have recently gained significant attention due to a growing body of evidence suggesting their involvement in cardiac remodelling such as fibrosis. ncRNAs can be found in the peripheral blood, indicating their potential as biomarkers for assessing HF severity. In this review, we critically examine recent advancements and findings related to the use of ncRNAs as biomarkers of HF and discuss their implication in fibrosis development.